Development of High Oil Yielding Niger Variety for Gujarat State: Development of High Oil Yielding Niger Variety for Gujarat State - P K JAGTAP; P M MISTRY; S P DESHMUKH (Journal of Oilseeds Research, 2023)
Deveolpment of high oil yielding Niger variety GNNIG-4 was done by mass selection from mutated population of RCR-317 (15kr) after subjecting the population to various evaluation trials. The present high yielding Niger cultivar is suitable for kharif /late kharif season in Gujarat as sole or intercrop. It has greenish purple stem colour with more oil content (37.77%) and oil yield (205 kg/ha). It has medium maturity (127 days) with bold seed size (4.08 gm/1000 seed). The variety is resistant to Alternaria and Cercospora leaf spot and also resistant to leaf eating catrepillar and semilooper under field condition. In various multilocation and coordinated trials, the genotype NMBP-1907 consistently recorded best performance over the checks. Under rainfed conditions the genotype gave 543 kg/ha seed yield which was 43.65, 34.07 and 41.40 per cent higher than the check varieties GN-2, GNNIG-3 and IGPN-2004-1. With high yield potential, medium maturity, resistance to diseases and pest, high oil, the Niger variety NMBP-1907 was identified for release and notified in 2021 under the name “GNNIG-4” for Kharif rainfed condition of Gujarat State.